Жуковский: [Художест. фильм] / Режиссеры В. Пудовкин, Д. Васильев, Операторы А. Головня, Т. Лобова, Композитор В. Шебалин - Гранберг А. (Кино. Наследие, 2001)
Экземпляры: ИСК (20021030) / Инвентарный номер: вкас401 / Цена: 108.60 / Сис.шифр: 85.374.9 / Авт.знак: Ж 86 / ГРНТИ: 18 / ББК: 85.374.9(2)